PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP KEBERHASILAN SISTEM GELANG ANTING DI PUSKESMAS LOSARI PEMALANG - Kamaliyah Rosyadah, Amanda; Santoso, R. Slamet; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This study aims to analyze the effect of system quality and information quality on the success of the Gelang Anting System at Puskesmas Losari Pemalang. With the background of high stunting cases in Indonesia and Pemalang Regency, as well as the Losari Health Center's efforts to develop technology-based innovations for stunting prevention. The research method used in this study is a quantitative approach with a sample of 78 respondents, using proportional random sampling technique and Likert scale for data collection. Hypothesis testing is done with Kendall's Tau-b correlation test to determine the effect partially, Kendall's W concordance to determine the effect simultaneously or together, and the coefficient of determination test to determine how strong the influence between variables. The results showed a positive and significant influence between system quality on system success, information quality on system success, and system quality and information quality together on system success with a significance of 0.000 <0.05. Based on the results of the study, it is recommended to improve the indicators of system quality and information quality to support the successful implementation of the Gelang Anting application.